Cyclic loading test of wall damping system with steel dampers. Issue 8 (August 2016) - Ahn, Hyung-Joon; Kim, Young-Ju; Bae, Jae-Hoon; Jung, In-Yong
Steel dampers, as an energy dissipation device, have been widely used to provide good seismic performance for building structures in strong seismic zones. Steel dampers for building structures are required to have adequate plastic deformation capacities so that they would not reach failure during strong ground motions and the aftershocks. However, the hysteretic behaviors of steel dampers considering the aftershock effects still remain unclear. In this study, wall damping system with a steel damper is proposed and tested. Steel damper in the wall damping system is installed horizontally at the bottom slit of the reinforced concrete wall aiming to dissipate energy during earthquake and prevent damage of the building structures, which could not only provide good seismic performance but could also be easily repaired after an earthquake. Test was conducted cyclically to simulate the effects of aftershocks, which can cause additional damage to already weakened structures from a main shock. Based on the test results, the seismic behavior of damping system was discussed with emphasis on the dissipated energy.